TEOLOGI PEMBEBASAN: MEMBACA KEBERAGAMAAN ISLAM DI INDONESIA PADA MASA PANDEMI COVID-19 - Danur Putut Permadi; Hanif Fitri Yantari (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Pandemic Covid-19 makes all activities experience the main paralysis in religious matters. One of them is a rule for keeping distance during prayer in an effort to break the chain of the Corona virus. Religious activities are required to be able to adjust government rules. If the Islamic community that lives in the environment is not free, it will not be able to religion and carry out full Islamic missions. In this context the Asghar Ali Engineer strongly criticizes the current era of Islamic theology which emphasizes more on metaphysical aspects rather than providing solutions in the practical life of Muslims. For Asghar Ali, the face of Islam now has two sides, namely Islam as a place to escape the trouble and Islam as a means of revolutionizing change. Asghar Ali said that if he wanted to make Islam a medium of revolution, there needs to be a liberation strategy which he calls the theology of Islamic liberation. This is done by reinterpretating the Qur'an through the analysis of "normative" and "contextual" aspects in order to obtain a new point of view. Based on a qualitative approach, this study found that during the Covid-19 outbreak there was a reinterpretation of religious diversity in Indonesia. Before the outbreak of Covid-19 Friday prayers by Muslims were understood mandatory without exception. But during the Covid-19 there was relief leaving Friday prayers. What also happened related to prayer in congregation. Previously, praying in congregation had to be a meeting, but because Covid-19, was allowed to be a distance during prayer in congregation.